Pengaruh Model Pembelajaran Self Organized Learning Environments (SOLE) Berbasis Blended Learning terhadap Kemandirian Belajar dan Hasil Belajar Kognitif Peserta Didik pada Materi Asam Basa - Ika Budyaningsih; Retno Aliyatul Fikroh (Jurnal Penelitian Pendidikan IPA, 2023)
Educators need learning models that can increase learning independence and cognitive learning outcomes of students during distance learning, but still pay attention to the government's appeal to inhibit the spread of the Covid-19 virus. One of the learning models that can improve learning independence and cognitive learning outcomes of students during distance learning is the Self Organized Learning Environments (SOLE) learning model based on blended learning. This study aims to examine whether there is an effect of the SOLE learning model based on blended learning on the learning independence of students on acid-base material and whether there is an effect of the SOLE learning model based on blended learning on the cognitive learning outcomes of students on acid-base material. This research is quasi-experimental. The sample in this study were students of class XI MIPA 1 and XI MIPA 2 SMAN 1 Godean. The sampling technique in this study was purposive sampling. The data collection technique was carried out using a student learning independence questionnaire sheet and test questions. The data analysis technique used was the Mann-Whitney test non-parametric statistics. Based on the results of the study there is an influence of the SOLE learning model based on blended learning on the learning independence of students on acid-base material based on the results of the questionnaire and there is no effect of the SOLE learning model based on blended learning on the cognitive learning outcomes of students on the material acid-base based on test results.